Root control of fungal communities and soil carbon stocks in a temperate forest. (October 2021) - Whalen, Emily D.; Lounsbury, Natalie; Geyer, Kevin; Anthony, Mark; Morrison, Eric; van Diepen, Linda T.A.; Le Moine, Jim; Nadelhoffer, Knute; vanden Enden, Lori; Simpson, Myrna J.; Frey, Serita D.
Abstract: Forest soil organic matter (SOM) is derived from both above- and belowground plant inputs, with a significant portion of this plant-derived organic carbon being processed by fungal communities prior to becoming SOM. Despite the central role of fungi in the processing of litter and root inputs, little is known about the relationship between fungal community composition and the relative conversion of aboveground litter versus root inputs into SOM. The Detrital Input and Removal Treatment (DIRT) experiments offer a system in which to test such questions, wherein aboveground litter and root inputs to forest soils are chronically excluded independently and in combination. In this study, we characterized fungal biomass (ergosterol), community composition (ITS2 metabarcoding), and community assembly (via null modeling) under root and litter exclusion treatments in a northern temperate forest DIRT experiment, and we related fungal community parameters to soil carbon. Root, but not litter, presence significantly differentiated fungal community composition and drove a more stochastic community assembly. Roots were associated with higher fungal biomass, particularly that of ectomycorrhizal and saprotrophic fungi, and with higher soil carbon stocks. The resulting strong positive correlation between fungal biomass and soil carbon appeared to be driven by saprotroph biomass in particular. We suggest that fungal communities are important mediators of the conversion of above- and belowground plant inputs into SOM, and that characterizing their composition may aid in understanding the relative importance of these plant input sources to SOM. Highlights: Roots, but not litter, significantly differentiated fungal community composition. Roots drove a more stochastic community assembly and increased community similarity. Fungal biomass was highest in +Root plots and positively correlated with soil C. This strong positive correlation appeared to be driven by saprotroph biomass.